(untitled) (Journal of Enam Medical College, 2012)
Background: HbA1c can be measured by different methods. Enzymatic, boronate affinity chromatographic and cation-exchange high performance liquid chromatographic (HPLC) methods are considered as gold standard methods. To make the test cost-effective many laboratories use the immunological method installed in a chemistry analyzer. Objective: To compare the values of HbA1c measured by high performance liquid chromatographic method and immunological method in two laboratory settings. Materials and Methods: This observational and comparative study was conducted in Bangladesh Institute of Health Sciences (BIHS) and Enam Medical College, Savar, Dhaka. HbA1c levels measured by HPLC in BIHS were compared with that measured by immunological method in Enam Medical College, Savar, Dhaka. p values <0.05 were considered significant. Results: Statistically no difference was observed in mean HbA1c% between two methods in <7.0% HbA1c group and 7.1-10.0% HbA1c group. Significant statistical difference was found in mean HbA1c >10.0% group, but it was within acceptable limit. Conclusion: HbA1c can be measured by immunological method installed in an automated chemistry analyzer to make the test cost-effective. But HPLC method is preferable. DOI: http://dx.doi.org/10.3329/jemc.v2i2.12839 J Enam Med Col 2012; 2(2): 62-66